2017
DOI: 10.3329/nimcj.v8i2.32551
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Postnatal Care Services among the Rural Women in Bangladesh

Abstract: Background : Low utilization of routine postnatal care (PNC) is an important determinant of high maternal and neonatal mortality in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
1
7
1
Order By: Relevance
“…The possible explanation for thisdue to poor accessto road to facilities and most women give birth at home. This finding was lower than study conducted in Rwanda 12.8% [14], Nigeria 16.9% [15], Bangladesh 73.8% [16],India 36.6%…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The possible explanation for thisdue to poor accessto road to facilities and most women give birth at home. This finding was lower than study conducted in Rwanda 12.8% [14], Nigeria 16.9% [15], Bangladesh 73.8% [16],India 36.6%…”
Section: Discussioncontrasting
confidence: 63%
“…Districts are even sub-divided into Kebeles (the lowest administrative units). There were 16,253 Kebeles. The total population of the nation reached 94.3 million in 2017.…”
Section: Study Area and Periodmentioning
confidence: 99%
“…15 In this study most of the respondents (34%) got information about PNC from private hospital which is different from other study where (32.5%) got from health workers . 16 This study revealed that among 200, 187(97.9%) used PNC, mother's who do not have knowledge on PNC services not utilize the services. This finding was consist with the study done in Uganda that revealed among those who were aware of the PNC services, a large proportion of mothers utilized the services.…”
Section: Discussionmentioning
confidence: 85%
“…Three PN visits were less as 17.5% in another study from Nepal, Chitwan 27 . Similarly a study conducted in Bangladesh, taken PNC more than three times in PP period was 29% 28 . Sri Lankan healthcare system may be more advanced than other regional countries.…”
Section: Background Characteristicsmentioning
confidence: 87%